2010
DOI: 10.1007/s10681-010-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of Pc68, a crown rust resistance gene in Avena sativa

Abstract: Crown rust, which is caused by Puccinia coronata f. sp. avenae, P. Syd. & Syd., is the most destructive disease of cultivated oats (Avena sativa L.) throughout the world. Resistance to the disease that is based on a single gene is often short-lived because of the extremely great genetic diversity of P. coronata, which suggests that there is a need to develop oat cultivars with several resistance genes. This study aimed to identify amplified fragment length polymorphism AFLP markers that are linked to the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Breeders then turned to exotic sources of resistance in wild Avena spp. The hexaploid wild animated oat, A. sterilis, was first used as a source because of its crossability with cultivated oat (8). However, the initial euphoria caused by an apparent abundance of new Pc genes soon turned to disappointment.…”
mentioning
confidence: 99%
“…Breeders then turned to exotic sources of resistance in wild Avena spp. The hexaploid wild animated oat, A. sterilis, was first used as a source because of its crossability with cultivated oat (8). However, the initial euphoria caused by an apparent abundance of new Pc genes soon turned to disappointment.…”
mentioning
confidence: 99%
“…This number is consistent with results from Oliver et al (2013) where 16 % of the SNP loci interrogated by the Illumina GoldenGate assay were polymorphic across six different mapping populations on average. Low polymorphism is a common characteristic to species with large genomes (Kulcheski et al 2010;Li et al 2000;Yu and Herrmann 2006). It has been suggested that the low genetic polymorphism found in crops such as oat and wheat is due to the evolution of the species (Bryan et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified seedling resistance genes that protect wild and cultivated oats against Pca, and at least 96 such genes have been characterised and given Pc designations (CDL, 2006; Kulcheski et al , 2010). A majority of the Pc resistance genes described to date have been derived from genotypes of hexaploid and diploid oat species, and have proven to be non‐durable.…”
Section: Introductionmentioning
confidence: 99%